PENGARUH KONTEN "RATUSAN MAHASISWA BER-KTP BANDUNG DIKETAHUI TERINFEKSI HIV AIDS" INSTAGRAM @FOLKATIVE TERHADAP PEMENUHAN KEBUTUHAN INFORMASI GENERASI Z (Survei Dilakukan Pada Followers Instagram Akun @Folkative) - Maria Rosaria Larasati, (2023)
This research is motivated by technological advances that are so great that they appear in the community in obtaining information. Instagram is one of the social media that is currently used by the public in seeking information and also the media in disseminating information. Therefore, @folkative as an alternative media that uses Instagram as a medium for disseminating information, containing the latest news that is busy in Indonesia, has become one of the information media that is widely followed by Indonesian people. This study aims to determine how much influence the content of the Instagram account @folaktive (variable X) has on meeting the information needs of generation Z (variable Y). The theory used in this research is the Uses and Gratification theory. The concepts in this study include new media, social media, Instagram, content, Generation Z, information needs. The research method of this research is quantitative. This research makes followers of the Instagram account @folkative as a population and uses a random sampling technique, with a total sample of 100 respondents. The results of this study indicate that there is a large influence between the content "Hundreds of students with ID cards in Bandung are known to be infected with HIV AIDS" on the fulfillment of Generation Z's information needs. This can be seen from the results that 63.3% of Generation Z's information needs are influenced by the content of the Instagram account @folkative, while the remaining 36.7% is influenced by other factors not examined. In addition, this research also shows that the content of the Instagram account @folkative has a significant influence on meeting the information needs of Generation Z. Based on the research that has been done, it is proven that there is a significant influence between the content "Hundreds of students with ID cards in Bandung are known to be infected with HIV AIDS" on the fulfillment of the information needs of Generation Z.